Core based tree multicast (M-CBT) approach in supporting mobility - Singh, Jaipal; Veeraraghavan, P.; Singh, S. (ACTA Press, 2004)
IP multicasting provides a mechanism for faster handoff support than Mobile IP. Coupled with its location independent addressing, multicasting is a viable alternative to support mobility in the Internet. This paper continues research into using IP multicasting in mobility. Our proposed scheme looks at enabling a mobile node to initiate two way communications with a corresponding node on a shared multicast tree. We use as much of the existing Internet architecture as possible by making the base station a member of the multicast group. The mobile is not directly connected to the tree but goes through the base station to send and receive packets. This paper explains the differences and advantages of our proposed scheme compared with other multicast based mobility schemes and Mobile IP.